2013
DOI: 10.1186/1749-8090-8-91
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume may predict early clinical outcome after coronary artery bypass grafting

Abstract: BackgroundAn elevated mean platelet volume is associated with increased platelet activation and thus may predict thrombotic events. The goal of this study was to investigate the association of the mean platelet volume and the major adverse events after coronary artery bypass surgery.MethodsBaseline clinical details and preoperative hematologic parameters were obtained prospectively in 205 consecutive patients undergoing coronary artery bypass surgery. Postoperative mortality and major adverse events were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…It was shown that activated platelets adhere to the endothelium, express adhesion molecules, and function in the induction of the immunological cascade [26]. Therefore, it has been reported in the literature that MPC can be used as an outcome prediction marker in cardiac diseases [4,27]. In a previous study [4] conducted at our hospital, the MPV cutoff value was obtained as 8.75 based on the study population's receiver operating analysis, and we used this value in the present study.…”
Section: Mean Platelet Volume (Mpv)mentioning
confidence: 98%
See 2 more Smart Citations
“…It was shown that activated platelets adhere to the endothelium, express adhesion molecules, and function in the induction of the immunological cascade [26]. Therefore, it has been reported in the literature that MPC can be used as an outcome prediction marker in cardiac diseases [4,27]. In a previous study [4] conducted at our hospital, the MPV cutoff value was obtained as 8.75 based on the study population's receiver operating analysis, and we used this value in the present study.…”
Section: Mean Platelet Volume (Mpv)mentioning
confidence: 98%
“…Therefore, it has been reported in the literature that MPC can be used as an outcome prediction marker in cardiac diseases [4,27]. In a previous study [4] conducted at our hospital, the MPV cutoff value was obtained as 8.75 based on the study population's receiver operating analysis, and we used this value in the present study. We found that MPV is an independent predictor for CAE (1.5 fold); however, similar to RDW, its prediction success was lower than that of NLR (1.5 versus 4.8).…”
Section: Mean Platelet Volume (Mpv)mentioning
confidence: 99%
See 1 more Smart Citation
“…24 During cardiopulmonary bypass multiple processes occur involving platelets, coagulation factors and vascular endothelium promoting the shift of risk from bleeding to thrombosis that manifest as multi-organ complications and worsens the outcome. 25 In 2000, Vuylsteke and his colleagues 26 found that the increased preoperative platelet count was associated with increased heparin resistance due to the increased capacity to produce platelet factor 4 that neutralizes heparin, the platelet count in patients who showed heparin resistance was {252 (221 -270) X 10 3 /mm 3 } while normal patients platelet count was {194 (165-223) X 10 3 /mm 3 }. In our study we found that the preoperative platelet count was higher in non survivors {296.87 ± 66.05 X 10 3 /mm 3 } compared to survivors {236.79 ± 66.92 X 10 3 /mm 3 } and this was supported by the results of Unal et al (2013) 25 who reported that the increased platelet count was correlated with adverse events after CABG with The reported platelet count in their patients with adverse events being 262 ± 66 X 10 3 /mm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is associated with a range of postoperative consequences (stroke, acute myocardial infarction), major side effects, re-hospitalization, duration of stay in the Intensive Care Unit and hospital stay, mortality 30 days after the intervention ( 5 ). Westenbrink et al ( 6 ) noted that every 1 mg/dl decrease in Hb was associated with a 13% increase in cardiovascular events and 22 % increase in all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%